Geração de energia elétrica a partir da concentração solar - Silva, Rafael Burd Teixeira da [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The current world's need for clean and renewable energy sources aligned with the strong Brazilian growth looking to diversify its electric power generation sources, highly dependent on hydropower and petroleum encourages the implementation of technologies that reach this growth with diversity and cleaning. The sun energy source is considered inexhaustible and can meet the demand for energy through thermo solar plants to generate electricity. Several technologies are being studied and developed in the world and they can be used to generate electricity from the solar concentration, but in Brazil its use is still not found commercially. It is therefore essential to understand these technologies and develop knowledge about them so they can be implemented in Brazil. This work brings an overview of the thermo solar generation in Brazil, showing the different technologies and a thermodynamic simulation of one of such technologies considering a hybrid plant with complementary generation biomass, aiming at the generation of 1 MW in the Brazilian Northeast
Keywords: Processos de fabricação; Energia - Fontes alternativas; Sistemas de energia eletrica; Renewable; Solar energy; Energy generation